Role of short-term estradiol supplementation in symptomatic postmenopausal COVID-19 females: A randomized controlled trial - Shikha Seth; Ritu Sharma; Pinky Mishra; Hariom Kumar Solanki; Monika Singh; Manisha Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Protective role of estrogen in COVID-19 was speculated once the epidemiological studies reported increased susceptibility of estrogen-deficient population - males and postmenopausal females to severe disease category and involvement of angiotensin-converting enzyme 2 receptors and renin-angiotensin-aldosterone system in pathophysiology. Materials & Methods: An open-label randomized controlled trial was planned to assess the efficacy of short-course oral estradiol in preventing the clinical progression to severe disease and reduce case-fatality rate and the hospital stay duration in estrogen-deficient postmenopausal women. The intervention group (n = 40) received 2 mg per day of estradiol valerate per orally for 7 days along with the standard care, while the control group (n = 40) received only the standard care. Results: A significant difference was observed in the rate of reverse transcriptase-polymerase chain reaction negativization in the intervention versus control group at day 5 and day 7 of admission (42.5% vs. 15%, P = 0.007; 72.5% versus 50%, P = −0.026). No significant difference was noted in the duration of hospitalization (P = 0.213). A significant decrease was noted in the mean values of inflammatory biomarkers - D-dimer, lactate dehydrogenase, and C-reactive protein on day 5 in the intervention group. Interleukin-6 also showed a declining trend on day 5 in the intervention group, while a rising trend was noted in the control arm. Only one case (2.5%) in the intervention group while seven in the control group (17.5%) progressed to the moderate category; however, the difference was not statistically significant (P = 0.057). Conclusion: Oral estradiol in postmenopausal females can be a novel and efficient option for managing nonsevere COVID-19 infection.